Epiphrenic Diverticula Mini-invasive Surgery: a Challenge for Expert Surgeons—Personal Experience and Review of the Literature. (June 2013) - Rossetti, G.; Fei, L.; del Genio, G.; Maffettone, V.; Brusciano, L.; Tolone, S.; Cimmino, M.; Moccia, F.; Terrone, A.; Romano, G.; Guerriero, L.; del Genio, A.
Background and Aims: While in the past, thoracotomy represented the traditional surgical approach for the treatment of epiphrenic diverticula, actually mini-invasive approach seems to be the preferred treatment as many series have been published in the recent years. This article describes the authors' experience with the laparoscopic approach for performing diverticulectomy, myotomy, and Nissen–Rossetti fundoplication. Material and Methods: From 1994 to 2010, 21 patients (10 men and 11 women), mean age 58.5 years (range 45–74 years), with symptomatic epiphrenic diverticulum underwent laparoscopic diverticulectomy, myotomy and Nissen–Rossetti fundoplication. Results: The mean operative time was 135 min (range = 105–190 min). Mean hospital stay was 14.2 days (range = 7–25 days). In 5 patients (23.8%), a partial suture staple line leak was observed. Conservative treatment achieved leak resolution in all the cases. One patient (4.8%) died of a myocardial infarction in the postoperative period. After a mean clinical follow-up period of 78 months (range = 6–192 months), excellent or good outcome was referred with no dysphagia in 16 patients (80%) and only mild occasional dysphagia in 4 patients (20%). Conclusions: Surgical treatment of epiphrenic diverticula remains a challenging procedure also by mini-invasive approach, with major morbidity and mortality rates. For this reason, indications must be restricted only to selected and symptomatic patients in specialized centers.